Performance Of Compressive Strength With 5% Coconut Shell As Fine Aggregate Replacement - Muhammad Hairie, Jonny (2023)
The production of concrete in the world is increasing rapidly day by day. It is caused by rapid and advanced human development. The human population is also increasing day by day. Therefore, many areas will be explored and many new settlements will be built. Due to the issues that occur, the demand for concrete will also increase from time to time and also the cost for its production will also increase. Due to the increase in concrete manufacturing, pollution also occurs such as the release of green gases and also leads to global warming. It will also lead to the reduction of natural materials such as aggregates and so on. Therefore, other materials need to be used as substitutes to produce concrete. The materials used must be in large quantities, for example using agricultural waste such as coconut shells. Society in Malaysia does not run away from the use of coconut in daily life. This use produces waste materials such as coconut shells. From the above problem which is related to concrete and coconut shell waste, it can be dealt with by using coconut shell as a substitute for concrete making material such as replacing the basic material for making concrete. By doing research, it can be done if a lot of research is done to produce concrete that contains waste materials so as to reduce agricultural waste. Overall, the replacement of basic materials producing concrete can overcome global issues, save costs and also make the environment clean and safe.